Avaliação da qualidade de vida de pessoas com complicações respiratórias na síndrome pós-Covid-19 - Mendonça, Larissa Bento de Araújo (2022)
Among the most common complications in people who develop post-COVID-19 syndrome are respiratory complications, with dyspnea and persistent cough being the most prevalent. Quality of life has become an important topic to be studied in people who have gone through the experience of having acquired COVID-19 and post-COVID-19 syndrome, as this disease has long-term consequences for people, interfering with their quality of life. life. The objective is to evaluate the quality of life of people who developed respiratory complications in the post-COVID-19 syndrome and its association with the social determinants of health. This is a case-control study carried out with 300 people who had COVID-19, residing in the states of Ceará, Maranhão or Pernambuco, divided into two groups: the Case group, consisting of 100 people who developed respiratory complications resulting from post- COVID-19 syndrome. COVID-19; and Control group, composed of 200 people who had COVID-19 but did not develop respiratory complications in the post-COVID-19 syndrome. Data collection was carried out in 2021 and 2022, from the sending of instruments through a monitoring software for patients with COVID-19, contemplating an instrument of social determinants of patients' health, the SF-QoL questionnaire. 36 and the Saint George Questionnaire on Respiratory Disease (QSGR). The homogeneity of the samples was verified and the normality of the variables was analyzed using the Kolmogorov-Smirnov test. Means were compared by parametric Student's t test and ANOVA, followed by Tukey's post hoc test. Associations between categorical variables were analyzed using the chi-square test. Correlation analyzes were performed using Pearson's correlation coefficients. Inferential analyzes with p<0.05 were considered statistically significant. The study was approved by the Research Ethics Committee. As a result, both groups, Case and Control, demonstrated homogeneity, not showing significant differences (p<0.05) between sociodemographic data. In the quality of life assessment, the Control group had a better quality of life in all domains of the SF-36 compared to the Case group, with a significant difference (p<0.05). In assessing the quality of life of people who had respiratory complications, according to the QSGR domains, the activity domain had the worst scores and the symptom domain had the best scores. A direct correlation was identified between the SF-36 domains (p<0.0001) as well as between the QSGR domains and an inverse correlation between the domains of the two questionnaires (p<0.0001). It is concluded that people who had COVID-19 and developed respiratory complications in the post-COVID-19 syndrome, had a worse quality of life, according to the SF-36 and QSGR domains, compared to people who had COVID-19 and who did not develop respiratory complications from post-COVID-19 syndrome.